Improving Learning Outcomes About the Human Circulatory System Through a Scientific Approach to Class V Students of SDN Arjosari - Helmi Cahyono (Universitas Sebelas Maret, 2020)
The purpose of this study was to determine the extent to which student learning outcomes improved and to determine the extent to which the scientific approach was applied in learning about the human blood circulation system in class V SDN Arjosari, Adimulyo District, Kebumen Regency. The research conducted was a Classroom Action Research (CAR) in three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting conducted a formative test to determine student learning outcomes. The first cycle was 22%, the second cycle increased 67% to 89% and the third cycle increased 11% to 100%. These results indicate that the scientific approach can improve student learning outcomes, especially Class V science muple at SDN Arjosari.